HUBUNGAN GLUKOSA URINE DENGAN KETON URINE PADA PENDERITA DIABETES MELLITUS DI KLINIK PRATAMA RAWAT JALAN BANDAR LOR KOTA KEDIRI - Hartati Tuna (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2023)
Background: Diabetes mellitus is a metabolic disorder characterized by impaired insulin secretion. In uncontrolled diabetics, the body is unable to convert blood glucose into energy, so the energy needed by the body will come from fat metabolism and ketones will be formed. The accumulation of ketone bodies produced by liver cells can cause metabolic acidosis if treatment is not enough, it becomes more serious and can lead to diabetic ketoacidosis (KAD). Objective: This study was conducted to determine the corelation between urine glucose and urine ketones in Diabetes Mellitus patients at the Clinic Pratama Rawat Jalan Bandar Lor City Kediri. Methods: The design of this study used a cross-sectional. The population is all elderly in the RT 07 RW 08 of Pojok Village, Mojoroto District, Kediri City, totaling 22 elderly. The research method used is Total Sampling. Analysis of the data used is Shapiro Wilk. Results: The average level of urine glucose examination results 43 mg/dl and urine ketone 0.07 mg/dl. Based on the Spearman Rank correlation test there is a relationship between urine glucose and urine ketones with a significant value of 0.001 or <0.05 and r = 0.619. Consultations and suggestions: The conclusion of this study is that there is a corelation between urine glucose and urine ketones in Diabetes Mellitus patients at the Clinic Pratama Rawat Jalan Bandar Lor City Kediri